Keselarasan Nilai Kepemimpinan Lokal dan Nasional: Studi Perbandingan Antara Ninik Mamak dan Ki Hadjar Dewantara - Eviana Liswardani Ayu (SMARTINDO, 2025)
This article aims to examine and compare the leadership values embodied by Ninik Mamak, the traditional leaders of the Minangkabau community, and Ki Hadjar Dewantara, a national figure in Indonesian education. Through a literature review and analysis of academic research, this study explores the fundamental similarities and differences in the principles, ethics, and leadership practices upheld by these two figures within their respective social and cultural contexts. The findings reveal that both Ninik Mamak and Ki Hadjar Dewantara emphasize morally grounded leadership, social responsibility, and leading by example. Ninik Mamak’s leadership is rooted in the customary principle of